Are SMC Complexes Loop Extruding Factors? Linking Theory With Fact. (3rd December 2018) - Baxter, Jonathan; Oliver, Antony W.; Schalbetter, Stephanie A.
Abstract : The extreme length of chromosomal DNA requires organizing mechanisms to both promote functional genetic interactions and ensure faithful chromosome segregation when cells divide. Microscopy and genome‐wide contact frequency analyses indicate that intra‐chromosomal looping of DNA is a primary pathway of chromosomal organization during all stages of the cell cycle. DNA loop extrusion has emerged as a unifying model for how chromosome loops are formed in cis in different genomic contexts and cell cycle stages. The highly conserved family of SMC complexes have been found to be required for DNA cis ‐looping and have been suggested to be the enzymatic core of loop extruding machines. Here, the current body of evidence available for the in vivo and in vitro action of SMC complexes is discussed and compared to the predictions made by the loop extrusion model. How SMC complexes may differentially act on chromatin to generate DNA loops and how they could work to generate the dynamic and functionally appropriate organization of DNA in cells is explored. Abstract : Numerous studies have suggested that SMC complexes can act as the enzymatic core of chromosomal machines that drive looping of DNA. Here, the authors discuss the current body of evidence available for the in vivo and in vitro action of SMC complexes, and compare them to the predictions made by the loop extrusion model.